Price behaviour of Tomato in Major Markets of Nagpur District - Deshmukh, Vedika S.; Shende, Dr. N. V.; Nagpure, Dr. S. C. (International Journal of Environment, Agriculture and Biotechnology, 2024)
This research undertakes a comprehensive analysis of trends, variability, and seasonal fluctuations in arrivals and prices as well as the interrelationship between arrivals and prices of selected vegetable in kalamna, kalmeshwar and kamthi Markets of Nagpur District, Maharashtra for the year (2014-2023) by utilizing secondary data sourced from the website (www.agmarknet.nic.in).An analysis of market arrivals and prices of Tomato reveals a positive trend in arrivals and prices across all the three Nagpur District markets, Although statistical significance was only observed in two markets excluding kalamna market. Highest variability in Tomato arrivals i.e 82.04 was recorded in kamthi APMC, Nagpur while Pt. Jawaharlal Nehru Market Yard, Kalamna, Nagpur saw the highest price variability i.e 86.30. In contrast lowest variability in Tomato arrival i.e 62.84 was recorded in Pt. Jawaharlal Nehru Market Yard ,Kalamna, Nagpur and lowest price variability i.e 80.20 was observed in kamthi APMC, Nagpur. Highest seasonal indices for Tomato arrivals and prices observed in December and October at Pt. Jawaharlal Nehru Market Yard, kalamna, Nagpur. March and July at kalmeshwar APMC, Nagpur and December and July at kamthi APMC, Nagpur. A statistically significant negative correlation was observed between arrivals and prices of Tomato in the Nagpur markets except for kalmeshwar market which shows positive correlation.